In Vitro and In Vivo Interactions of DNA Ligase IV with a Subunit of the Condensin Complex - Przewloka, Marcin R. (The American Society for Cell Biology, 2003)
Several findings have revealed a likely role for DNA ligase IV, and interacting protein XRCC4, in the final steps of mammalian DNA double-strand break repair. Recent evidence suggests that the human DNA ligase IV protein plays a critical role in the maintenance of genomic stability. To identify protein–protein interactions that may shed further light on the molecular mechanisms of DSB repair and the biological roles of human DNA ligase IV, we have used the yeast two-hybrid system in conjunction with traditional biochemical methods. These efforts have resulted in the identification of a physical association between the DNA ligase IV polypeptide and the human condensin subunit known as hCAP-E. The hCAP-E polypeptide, a member of the Structural Maintenance of Chromosomes (SMC) super-family of proteins, coimmunoprecipitates from cell extracts with DNA ligase IV. Immunofluorescence studies reveal colocalization of DNA ligase IV and hCAP-E in the interphase nucleus, whereas mitotic cells display colocalization of both polypeptides on mitotic chromosomes. Strikingly, the XRCC4 protein is excluded from the area of mitotic chromosomes, suggesting the formation of specialized DNA ligase IV complexes subject to cell cycle regulation. We discuss our findings in light of known and hypothesized roles for ligase IV and the condensin complex.